The Office of Tax Simplification: Looking back and looking forward - Tracey Bowler (Institute for Fiscal Studies (IFS), 2014)
[Introduction] The Office of Tax Simplification (OTS) was set up by the current government more than four years ago. With less than one year left of its initial fixed term, this discussion paper considers what the OTS has achieved to date and what can be learnt about the impact of the OTS on simplification of the tax system. It considers what conclusions can be drawn from the past four years in assessing whether the next government should continue with the OTS and what changes to its operation could be considered. The paper is written for the Tax Law Review Committee (TLRC) of the Institute for Fiscal Studies.
Additional information: TLRC Discussion Paper No. 11.
Keywords: 330